Excess benign melanocytic naevi after chemotherapy for malignancy in childhood. Issue 6691 (8th July 1989) - Hughes, B. R.; Cunliffe, W. J.; Bailey, C. C.
Abstract : OBJECTIVE–To see whether children who have had chemotherapy develop increased numbers of moles. DESIGN–Blind assessment of patients having chemotherapy and subsequent comparison with the first suitable patients matched for age and sex who were attending the clinic during the same period after having completed treatment. Controls were obtained the following year by taking the first suitable patients attending a routine dermatology outpatient clinic who matched the study groups for age and sex. SETTING–Referrals to a paediatric oncology clinic and a dermatology clinic at two city hospitals. PATIENTS–The group receiving chemotherapy comprised all 32 patients with acute lymphatic leukaemia, lymphoma, and rhabdomyosarcoma who were attending the paediatric oncology clinic on two mornings a week during October 1987 to March 1988. The group who had completed treatment comprised 32 patients who were attending for follow up during the same period and who matched the first group for age and sex. Thirty two other patients attending the dermatology outpatient clinic with unrelated skin conditions served as controls. END POINT–Definite increase in numbers of moles on children after a course of chemotherapy. MEASUREMENTS AND MAIN RESULTS–Moles were counted by one observer on defined areas of the body and divided into those less than 3 mm and greater than or equal to 3 mm diameter. Patients receiving chemotherapy had a similar number of moles to the control group. By contrast patients who had completed chemotherapy had significant increases both in moles less than 3 mm and greater than or equal to 3 mm and in the total number of moles. These patients were more likely to have moles on acral sites. CONCLUSIONS–Children with substantially increased numbers of moles (benign melanocytic naevi) after successful chemotherapy for malignancy may have an increased risk of melanoma. They should be offered prolonged surveillance and cautioned about exposure to ultraviolet light.